Respuesta :

csms4

Answer: Number one is 4, number 2 is no solution

Step-by-step explanation:

1.

First you have to simplify both sides of the equation.

5x−(x+3) = 1/3 (9x+18)−5

5x+−1(x+3)=1/3 (9x+18)−5 (Distribute the Negative Sign)

5x+−1x+(−1)(3)= 1/3 (9x+18)−5

5x+−x+−3= 1/3 (9x+18)−5

5x+−x+−3=(1/3)(9x)+(1/3)(18)+−5(Distribute)

5x+−x+−3=3x+6+−5

(5x+−x)+(−3)=(3x)+(6+−5)(Combine Like Terms)

4x+−3=3x+1

4x−3=3x+1

Then you have to subtract 3x from both sides.

4x−3−3x=3x+1−3x

x−3=1

Add 3 to both sides.

x=4

2. There is no solution